NEC in Twin Pregnancies: Incidence and Outcomes - Sathyaprasad C Burjonrappa; Brian Shea; Diya Goorah (EL-Med-Pub, 2014)
Background: Necrotizing Enterocolitis (NEC) is the most common gastrointestinal emergency in neonates. Previously established risk factors for the development of NEC include prematurity and low birth weight. However, it is not clear to date as to whether the etiology of NEC is due to host, environmental, or yet other unknown factors. We analyzed the differences in incidence of NEC in twin pregnancies to further clarify its etio-pathogenesis. Methods: After IRB approval, a retrospective search of the medical records of the Department of Pediatric Surgery was done to identify all the neonates treated for surgical NEC from 2006-2013. Patients that had been treated for NEC elsewhere and subsequently transferred in to our facility were excluded. The medical records of the resulting 45 patients were then analyzed for demographics, antenatal screening, risk factors, treatment (medical and surgical), and outcomes. The resulting data was then analyzed using relative risk calculations and standard statistical tests. Results: Of the 45 patients who developed surgical NEC, 9 neonates (20%) were born of a twin pregnancy. There were no cases in which both twin A and twin B developed NEC. NEC in twin pregnancy neonates showed a female preponderance (p<0.0001) and developed universally in the first born of the twins. Birth weight, time of onset of NEC, hospital stay and mortality were similar between twin and non-twin NEC. There was an average lead-time of three weeks to development of NEC in both singletons and twin pregnancies. Conclusion: There is a remarkable higher incidence of NEC amongst twins. Abnormal colonization of the gastrointestinal tract appears to be an immediate postpartum event. NEC in twin pregnancy does not appear to have a deleterious outcome compared to NEC in singleton pregnancy.